2006
DOI: 10.1080/14786410500162047
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical studies and antibacterial activity of Centaurium pulchellum Druce

Abstract: Two isocoumarin derivatives, one new, erythricin (1) and a known erythrocentaurin (2) were isolated from the whole plant of Centaurium pulchellum Druce. The 13C-NMR data of compound 2 are described. The structures of compounds 1, 2 were elucidated on the basis of spectral analysis including 2D-NMR experiments. Antibacterial and brine shrimp lethality assays are also described on the fractions of the plant extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…All the tested extracts possessed antibacterial activity with MICs (minimum inhibitory concentrations) and MBCs (minimum bactericidal concentrations) in the range of 0.05-0.2 mg mL -1 , depending on the bacterial species (Table 1), showing similar effects as the commercial antibiotics Streptomycin and Ampicillin. These results indicate that methanol extracts of C. pulchellum were more powerful antibacterial agent than previously reported for chloroform, ethyl acetate and ethanol extracts of this species [3]. Despite the fact that selected populations significantly differ in their quantitative secoiridoid content, no major differences in antibacterial activities were observed.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…All the tested extracts possessed antibacterial activity with MICs (minimum inhibitory concentrations) and MBCs (minimum bactericidal concentrations) in the range of 0.05-0.2 mg mL -1 , depending on the bacterial species (Table 1), showing similar effects as the commercial antibiotics Streptomycin and Ampicillin. These results indicate that methanol extracts of C. pulchellum were more powerful antibacterial agent than previously reported for chloroform, ethyl acetate and ethanol extracts of this species [3]. Despite the fact that selected populations significantly differ in their quantitative secoiridoid content, no major differences in antibacterial activities were observed.…”
supporting
confidence: 56%
“…The traditional medicine of Egypt recommends this species for the treatment of various disorders [1]. This annual herbaceous plant, like the majority of Centaurium species, is a rich source of bitter secoiridoid glycosides, xanthones and β-monoglycosides [2] and is reported to have some antibacterial properties [3].…”
mentioning
confidence: 99%
“…By using the well diffusion method, the crude ethyl acetate extracts of endophytic fungi suspended in Dimethyl Sulfoxide (DMSO) were screened against bacterial pathogens, and the zones of inhibition were measured [ 22 , 23 ]. Amoxicillin was used as positive control, while dimethyl sulfoxide (DMSO) was used as negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Chemotaxonomy and pharmacology study reports that swertiamarin is usually found in Gentianaceae family (Jensen, & Schripsema, 2002). It was found that many plants in Gentianaceae family containing a secoiridoid glycoside, swertiamarin possessed antibacterial properties such as Centaurium species (Bibi et al, 2006;van der Sluis, 1985). and Enicostema species (Perumal et al, 2022;Pillai et al, 2020;Vishwakarma et al, 2004).…”
Section: Introductionmentioning
confidence: 99%